Youth Empowerment Program Based on Digital Leaflet to Improve Help-Seeking Behavior Related to Mental Health Issues Among Students - Agusta Dian Ellina; Muhammad Ali Sodik (STIKes Patria Husada Blitar, 2026)
Mental health problems among adolescents have become a growing global concern. This study aims to examine the effectiveness of a youth empowerment program using digital leaflets to improve help-seeking behavior related to mental health issues among students. Technological progression and digital media saturation in the lives of adolescents provide avenues for addressing these issues anew. Reaching adolescents (and other target groups) in their communities via digital media. This study focused on the ‘One Group Pretest-Post Test Design’ framework which employs a quantitative technique and uses a quasi-experimental design. This framework was able to determine whether or not there was any impact from the intervention. Using a pretest-posttest design with 312 students, statistical analysis showed a significant increase in help-seeking behavior after the digital leaflet intervention. The resulting significance level (p-value) was 0.000, which is significantly lower than the 0.05 significance level (α). This indicates that the difference in mean scores between the pretest and posttest did not occur by chance but is a real effect of the empowerment program. These findings suggest that digital media can be an effective tool for mental health education among adolescents.